Pengaruh Suhu Reaksi Dan Kecepatan Pengadukan Pada Sintesa Hidroksiapatit Dari Kulit Kerang Darah (Anadara Granosa) Dengan Metode Hidrotermal Suhu Rendah - Dewi Indah Pratiwi; Ahmad Fadli; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Hydroxyapatite (HA) is a ceramic material that widely used for bone implants as biocompatible and bioactive properties. Sea shells can be used as a source of calcium to produce hydroxyapatite. The purpose of this research was to determine the effect of rate stirrer and the reaction temperature on the synthesis of hydroxyapatite from sea shells with a low temperature hydrothermal method. The procedure was started with calcining sea shells into CaO at a temperature of 1000oC for 24 hours. Then 55.63 g of NH4H2PO4 was dissolved in 600 mL of water and 45.91 g of CaO was added into the solution at temperature variation of 70°C, 80oC, 90oC and stirring rate of 200 rpm, 250 rpm, 300 rpm until it forms a paste. The paste was dried in an oven at 120oC for 15 hours. Then the dried paste was crushed and calcined at a temperature of 900oC for 1 hour. The results showed that the size of hydroxyapatite crystals at 70°C is 63.43 nm, while the crystal with the size of 52.48 nm obtained when the temperature was increased to 90oC. The rate of stirrer of 200 rpm, the crystal with the size of 62.92 nm obtained, it decrease to 52.48 nm when the stirring rate increased 300 rpm. FTIR analysis showed that the hydroxyapatite is formed at the calcination temperature of 900°C. HA at a reaction temperature of 90oC with the stirring rate of 300 rpm to meet the standards as a bone filler (bone filler) synthetic. Keywords: Crystallinity, Hydrothermal, Hydroxyapatite and Sea Shells